Two‐site evaluation of the diagnostic performance of the Sysmex XN Body Fluid (BF) module for cell count and differential in Cerebrospinal Fluid. (3rd September 2017) - Buoro, S.; Peruzzi, B.; Fanelli, A.; Seghezzi, M.; Manenti, B.; Lorubbio, M.; Biagioli, T.; Nannini, S.; Ottomano, C.; Lippi, G.
Abstract: Introduction: Cellular analysis in cerebrospinal fluid (CSF) provides important diagnostic information in many pathological settings. The aim of this two‐site study was to evaluate the Sysmex XN Body Fluid mode (XN‐BF) for cell analysis of CSF compared to light microscopy (LM). Methods: Two hundred and seven consecutive CSF samples were analyzed in parallel with XN‐BF and LM. The study also included the estimation of the limit of blank (LoB), limit of detection (LoD), limit of quantitation (LoQ), carry‐over and linearity of XN‐BF module. Results: LoQ of white blood cells (WBC) was 3×10 6  cells/L; linearity was good and carry‐over negligible. XN‐BF parameters were compared to LM for the following cell classes: total cells, WBC, polymorphonuclear (PMN), and mononuclear (MN) cells. The bias ranged from 1.3 to 15.2×10 6   cells/L. The receiver operating characteristics curve analysis for WBC showed an area under the curve of 0.98, and the global diagnostic agreement was 95% at a cutoff of 5×10 6   cells/L. Conclusions: XN‐BF provides rapid and accurate counts in clinically relevant ranges of CSF values, thus providing a valuable alternative to conventional LM analysis. However, microscopic review remains advisable in samples with abnormal cell counts or high fluorescent (HF‐BF) cell parameter exceeding 5×10 6   cells/L.